Cross one single body 49 tissues single-cell transcriptome reveals detailed macrophage heterogeneity during pig pregnancy - Chen, Xiaoyun; Lai, Chenliang; Cai, Liping; Huang, Lusheng (Frontiers in Immunology, 2025)
IntroductionPregnancy involves complex physiological adaptations across maternal organs and the immune system to support fetal development. Macrophages play a dual role during pregnancy: defending against pathogens and supporting tissue adaptation. However, comprehensive and in-depth studies of cross-tissue transcriptional heterogeneity of macrophages during healthy pregnancy at the single-cell level remain elusive.MethodsWe performed single-cell RNA sequencing (scRNA-seq) to profile macrophages from a healthy pregnant pig across 49 tissues. Immunofluorescence was performed to verify the specific expression of transcription factors.ResultsIn this study, we generated a macrophage atlas containing 114,881 macrophages from 49 tissues/organs within one single healthy pregnant pig, identified 33 subtypes, and revealed extensive tissue-specific diversity. We observed significant heterogeneity of macrophage subtypes across five different anatomical sites of adipose tissue. Notably, the Mφ MARCO+ subtype, primarily derived from mesenteric adipose tissue, showed higher activity in pattern recognition receptor signaling pathways compared to subtypes in other tissues, including different fat depots. Cross-tissue analysis revealed distinct expression patterns of transcription factors, cytokines, and cell surface receptors, including the transcription factor PLSCR1, specifically expressed in lung macrophages and verified by immunofluorescence. Cross-species analysis unveiled conservation and heterogeneity among macrophages in pigs, humans, and mice.ConclusionWe constructed a multiple-tissue single-cell transcriptome atlas of macrophages in one single healthy pregnant pig, revealing their molecular differences and commonalities across tissues and species. Our study provides a valuable resource for understanding macrophage diversity and tissue-specific macrophage adaptations during pregnancy in pigs.